Would kazakh citizens support a milk co-operative system? - Kaliyeva, Samal; Areal, Francisco Jose; Gadanakis, Yiorgos (My University, 2021)
We estimate the monetary value of a policy aimed at increasing rural co-operative production in Kazakhstan to increase milk production. We analyse the drivers associated with public support for such policy using the contingent valuation method. The role of individuals’ psychological aspects, based on the reasoned action approach, along with individuals’ views on the country’s past regime (i.e., to the former Soviet Union), their awareness about the governmental policy, their sociode-mographic characteristics, and household location on their willingness to pay (WTP) for the policy is analysed using an interval regression model. Additionally, we examine changes in individuals’ WTP before and during the COVID-19 pandemic. The estimated total economic value of the policy is KZT 1335 bn for the length of the program at KZT 267 bn per year, which is approximately half the total program budget, which includes other interventions beyond the creation of production co-operatives. The total economic value of the policy would equal the cost of the whole program after 10 years, indicating public support for this policy amongst Kazakh citizens. Psychological factors, i.e., attitude, perceived social pressure, and perceived behavioural control, and the respondents’ awareness of the policy and views on the Soviet Union regime are associated with their WTP. Sociodemographic factors, namely, age, income, and education, are also statistically significant. Finally, the effect of the shocks of COVID-19 is negatively associated with the respondents’ WTP.
Keywords: co-perative creation policy; contigent valuation; reasoned action approach; Kazakhstan; COVID-19